Em busca da imagem videojográfica: uma cartografia das imagens de jogos digitais de 1976 a 2017 - Menezes, João Ricardo de Bittencourt (Universidade do Vale do Rio dos Sinos, 2018)
The main goal of this research was to develop videogamegraphics image concept proposing it as a joint between three layers: machine,ludic and audiovisual. For this, a methodological process was constructed that combined quantitative techniques and applicable in big data in cultural analytic, developed by Lev Manovich and articulated to an ontological perspective on the digital games proposed by Alexander Galloway.He proposes to put the games in a framework composed of two axes (diegetic/non-diegetic and operator/machine) that generate four forms of act game: diegetic machine, nondiegetic machine, diegetic operator and nondiegetic operator. From theoretical point of view, we start from understanding the playing phenomenon as a virtuality that is updated in different ways including machines created by man with purpose of playing.We have identified, from an archaeologically perspective inspiration, machines are unknown and related to digital games context of as the first updates of videogamegraphics image, including these machines of the digital era also part of a mediatization process produces countless contents derived from game performance. The role of the pixel in technocultural revolution is linked to an exponentiality of the presence of these technical images of the game, has been perceived, which contributes to the convening of cultural analytics as a way to account for this profusion. Its use allowed the creation of first movement of analysis, through a series of cartographies on the game images. So, we start to understand - from a conceptual proposal on videogamegraphics image - how this one was updated in the technical images of games created between 1976 and 2017. A second movement was adopted, for which frames methodology proposed by Kilpp and worked on in the research group Audiovisualities and Technoculture: Communication, Memory and Design, in order to observe cartography results through generation of mean images. In addition to the considerations developed in the first movement, it was understood that the videogamegraphics images are updated in their three layers as ethicities and with four great signification, of frames that around them - the platforms, the instruments of graphical interface, the diegese and the magic circle.These territories are framed that we can understand how their senses are created and, consequently, reflecting in the way of updating the ethicities in the videogamegraphics images. The technical surfaces frame the platforms; gadgets, information panels, dialog boxes and action bars are framed by graphics user interface instruments. Already, diegese is an important frame of audiovisuality framed also by dialog boxes, decorative panels and diegetic panels. And finally, the magic circle, recurrent and sometimes excessively dominant in the reflection on the playing act, is now perceived as a frame that enters into tension with the others through the same proposed frames.
Keywords: Jogos digitais; Imagem videojográfica; Cultural analytics; Metodologia das molduras; Comunicação; Digital games; Videogamegraphics image; Cultural analytics; Frames methodology; Communication; ACCNPQ::Ciências Sociais Aplicadas::Comunicação